Landscaping in Florida Shade - Sydney Park Brown (EDIS)
Trees and the shade they cast provide welcome relief from Florida’s intense sun and heat, but gardening in shade can be challenging. This 4-page fact sheet has some pointers for meeting these challenges and lists of shade-tolerant plants. Written by Sydney Park Brown, and published by the UF Department of Environmental Horticulture, February 2012.